2012
DOI: 10.1155/2012/474351
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of Drebrin A, an F-Actin Binding Protein, in Reactive Synaptic Plasticity after Pilocarpine-Induced Seizures: Functional Implications in Epilepsy

Abstract: Several neurological disorders characterized by cognitive deficits, including Alzheimer's disease, down syndrome, and epilepsy exhibit abnormal spine density and/or morphology. Actin-based cytoskeleton network dynamics is critical for the regulation of spine morphology and synaptic function. In this paper, I consider the functions of drebrin A in cell shaping, spine plasticity, and synaptic function. Developmentally regulated brain protein (drebrin A) is one of the most abundant neuron-specific binding protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 110 publications
(141 reference statements)
1
12
0
Order By: Relevance
“…These results would therefore suggest that spectrin was truncated by calpain-1 activation in a relatively small subset of neurons, while PTEN would be degraded by calpain-2 activation in a much broader population of neurons. Our results also confirmed that drebrin, a neuron-specific F-actin binding protein, is also a calpain substrate, and is degraded following KA-induced seizure activity, a finding corroborating results indicating that drebrin levels were decreased in a pilocarpine model of epilepsy ( Ferhat, 2012 ). As the pattern of changes for drebrin was very similar to that for PTEN, we therefore suggest that drebrin was also cleaved by calpain-2 in the hours following seizure initiation.…”
Section: Discussionsupporting
confidence: 89%
“…These results would therefore suggest that spectrin was truncated by calpain-1 activation in a relatively small subset of neurons, while PTEN would be degraded by calpain-2 activation in a much broader population of neurons. Our results also confirmed that drebrin, a neuron-specific F-actin binding protein, is also a calpain substrate, and is degraded following KA-induced seizure activity, a finding corroborating results indicating that drebrin levels were decreased in a pilocarpine model of epilepsy ( Ferhat, 2012 ). As the pattern of changes for drebrin was very similar to that for PTEN, we therefore suggest that drebrin was also cleaved by calpain-2 in the hours following seizure initiation.…”
Section: Discussionsupporting
confidence: 89%
“…Accumulating evidence suggests a link between actin remodeling and complex neurological disorders [Kojima and Shirao, ; Ivanov et al, ]. Cofilin upregulation followed by the translocation of drebrin A from DS was proposed to be part of a pathological pathway relevant to Alzheimer's disease (AD), Down syndrome, and epilepsy [Kojima and Shirao, ; Ferhat, ]. This pathway, which was suggested to lead to spine shrinkage and the impairment of higher order brain function, can be a potential therapeutical target for complex brain disorders [Zhou et al, ; Cho et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the detailed molecular mechanism of TLE is still unclear. Recent experimental evidence demonstrated that abnormal synaptic plasticity, including structural aberrations in dendrites of neurons, mossy fiber sprouts (MFS), and formation of anomalous excitatory loop in hippocampus are involved in pathology of TLE (Epsztein et al, 2005;Fang et al, 2011;Ferhat, 2012;Lukasiuk and Pitkanen, 2012). The unusual neural networks may cause abnormal discharge in the brain, which leads to recurrent seizures and long-time maintenance (Fernandez-Torre, 2002).…”
Section: Introductionmentioning
confidence: 99%